Synthesis of new 6-{[ω-(dialkylamino(heterocyclyl)alkyl]thio}-3-R-2H-[1,2,4]triazino[2,3-c]quinazoline-2-ones and evaluation of their anticancer and antimicrobial activities - Berest, G. G.; Voskoboynik, O. Yu.; Kovalenko, S. I.; Antypenko, L. M.; Antypenko, O. M.; Shvets, V. M.; Katsev, A. M. (My University, 2012)
Several novel 6-thio-3-R-2-oxo-2H-[1,2,4]triazino[2,3-c]quinazoline-based compounds containing an ω-(dialkylamino(heterocyclyl)]alkyl fragment were synthesized to examine their anticancer activity. Some of the 6-{[ω-(hetero-cyclyl)alkyl]thio}-3-R-2H-[1,2,4]triazino[2,3-c]quinazoline-2-ones (3.1-3.10) were obtained by the nucleophilic substitution of 6-[ω-halogenalkyl]thio-3-R-2H-[1,2,4]triazino[2,3-c]quinazoline-2-ones (2.1-2.8) with azaheterocycles. Alternatively, compounds 3.1-3.22 were synthesized by alkylation of 3-R-6-thio-2/-/-[1,2,4]triazino[2,3-c]quinazoline-2-ones potassium salts (1.1-1.4) with (2-chloro-ethyl)-N,N-dialkylamine hydrochlorides or 1-(2-chloroethyl)heterocycle hydrochlorides. The structures of compounds were elucidated by 1H, 13C NMR, LC-MS and EI-MS analysis. Then anticancer and antibacterial, biolumi-nescence inhibition of Photobacterium leiognathi Sh1 activities of the substances were tested in vitro. It was found that compound 3.18 possessed a wide range of anticancer activity against 27 cell lines of cancer: non-small cell lung, сolon, CNS, ovarian, renal, prostate, breast, melanoma and leukemia (log GI50 < -5.65). The “structure-activity” relationship was discussed. COMPARE analysis for synthesized anticancer active compounds was performed.
Keywords: 2H-[1,2,4]Triazino[2,3-c]quinazolin-2-one; Bioluminescence inhibition; Chemotherapeutic; Antibacterial; Anticancer; Cytostatic; COMPARE; SAR